A qualitative study on the experience of nurses participating in new media health science popularization (护士参与新媒体健康科普真实体验的质性研究) - LI Ting (李婷); XU Jianwen (徐建文); QIANG Hong (羌虹); WEI Xiaoxiao (卫笑笑); WANG Juan (汪娟); WANG Jingting (王婧婷) (中西医结合护理)
Objective To understand the experience and problems of nurses participating in new media health science popularization. Methods Using the qualitative research method of phenomenology, semi-structured interviews were conducted with 14 nurses who participated in the production and promotion of new media health science popularization. Results The real experience of nurses participating in new media health science popularization included 4 themes and 13 sub-themes. The 4 themes included: the improvement of nurses' sense of professional value; the improvement of nurses' new media health science popularization ability; the difficulties of nurses in new media health science popularization; perception Patients have complex science needs. Conclusion Nurses had benefited experience and encountered some difficulties in participating in new media health science popularization. Managers should integrate resources, improve the support system, encourage nurses to participate in new media health science popularization, enhance their sense of professional value and comprehensive ability, and build satisfaction High-quality new media health science popularization works with complex needs of patients. (目的 了解护士参与新媒体健康科普的体验及存在问题。方法 采用现象学质性研究方法, 对14名全流程参与新媒体健康科普制作和推广的护士进行半结构式访谈。结果 护士参与新媒体健康科普真实体验包括4个主题和13个亚主题, 4个主题包括: 护士职业价值感提升; 护士新媒体健康科普能力提升; 护士在新媒体健康科普中的困难; 感知到患者存在复杂科普需求。结论 护士参与新媒体健康科普存在获益体验, 也遇到一些困难。管理者应整合资源, 完善支持系统, 促进护士参与新媒体健康科普的同时, 提升其职业价值感及综合能力, 构建满足患者复杂需求的高质量新媒体健康科普作品。)